Optogenetically Activatable MLKL as a Standalone Functional Module for Necroptosis and Therapeutic Applications in Antitumoral Immunity - Da‐Hye Jeong; Seokhwi Kim; Han‐Hee Park; Kyoung‐Jin Woo; Jae‐Il Choi; Minji Choi; Jisoo Shin; So Hyun Park; Myung‐Wook Seon; Dakeun Lee; Jong‐Ho Cha; You‐Sun Kim (Advanced Science)
Abstract Necroptosis plays a crucial role in the progression of various diseases and has gained substantial attention for its potential to activate antitumor immunity. However, the complex signaling networks that regulate necroptosis have made it challenging to fully understand its mechanisms and translate this knowledge into therapeutic applications. To address these challenges, an optogenetically activatable necroptosis system is developed that allows for precise spatiotemporal control of key necroptosis regulators, bypassing complex upstream signaling processes. The system, specifically featuring optoMLKL, demonstrates that it can rapidly assemble into functional higher‐order “hotspots” within cellular membrane compartments, independent of RIPK3‐mediated phosphorylation. Moreover, the functional module of optoMLKL significantly enhances innate immune responses by promoting the release of iDAMPs and cDAMPs, which are critical for initiating antitumor immunity. Furthermore, optoMLKL exhibits antitumor effects when activated in patient‐derived pancreatic cancer organoids, highlighting its potential for clinical application. These findings will pave the way for innovative cancer therapies by leveraging optogenetic approaches to precisely control and enhance necroptosis.